Fully-iodinated bridged pyrroles as high thermostable energetic biocidal materials - Xin-yuan Zhao; Xun Zhang; Hao-tian Yu; Yan Liu; Si-ping Pang; Chun-lin He (Energetic Materials Frontiers)
Pyrrole is one of the important versatile skeletons for functional materials, fully-substituted pyrroles can achieve multiple substitutions. But, spatial site resistance effects make its synthesis difficult. In this work, a series of fully-iodinated bridged pyrroles (compounds 8–13) as energetic biocidal compounds were synthesized through two-step. They show high iodine content of 82.98 %–88.02 %, and high thermal stability (Td: 267–344 °C) which is a significantly improved compared to 2,3,4,5-tetraiodo-1H-pyrrole (TIPL, Td: 168 °C). Furthermore, good detonation pressure (P) and detonation velocity (D) were realized, showing great prospective for applications as potential energetic biocidal materials.